1992
DOI: 10.1007/bf00145376
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between alcohol consumption and positivity for antibodies to hepatitis C virus on the risk of liver cirrhosis: A case-control study

Abstract: To assess the risk of developing liver cirrhosis associated with alcohol consumption, HBV and HCV infection markers, we carried out a case-control study involving 115 patients admitted to the medical departments of the general hospitals in the province of L'Aquila (Abruzzo, Italy) who received for the first time the diagnosis of liver cirrhosis, and 167 controls randomly selected among patients admitted to the same hospitals as the cases. Alcohol intake was measured in all 282 subjects using an already validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…23 We also found synergism between HCV infection and alcohol drinking in causing HCC, as suggested by computation Concurrent HBV and HCV infection was a rare event in this study, since only 3 cases were observed instead of the of the S. This result is in contrast with the findings of two case-control studies on the risk of liver cirrhosis. 12,30 How-15 expected under the hypothesis of independence (test based on binomial distribution: P õ .001; 95% CI of the 3 ever, these and our studies report imprecise RR estimates, due to the small number of controls with both exposures, cases observed: 0-8). This finding suggests an interference between the two viruses, which is in line with observations which are compatible with both additive and more than additive effects.…”
Section: Laboratory Methodsmentioning
confidence: 53%
See 1 more Smart Citation
“…23 We also found synergism between HCV infection and alcohol drinking in causing HCC, as suggested by computation Concurrent HBV and HCV infection was a rare event in this study, since only 3 cases were observed instead of the of the S. This result is in contrast with the findings of two case-control studies on the risk of liver cirrhosis. 12,30 How-15 expected under the hypothesis of independence (test based on binomial distribution: P õ .001; 95% CI of the 3 ever, these and our studies report imprecise RR estimates, due to the small number of controls with both exposures, cases observed: 0-8). This finding suggests an interference between the two viruses, which is in line with observations which are compatible with both additive and more than additive effects.…”
Section: Laboratory Methodsmentioning
confidence: 53%
“…was similar to that reported among subjects hospitalized for diseases not associated with alcohol consumption in casecontrol studies carried out in Italy on the risk of cirrhosis. 11,12 jects who were anti-HCV positive without HCV RNA were vanced liver diseases have a higher prevalence of HBV markers than alcoholics with less severe forms of liver disease. 8 similar to those features observed in subjects who were anti-HCV negative.…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…As compared to ALD patients without HCV infection, those ALD patients with HCV infection have more severe histological features (83), have decreased survival (81), and develop their disease at a younger age (84). The prevalence of HCV also increases proportionally as the liver injury becomes more severe (85-88) with the relative risk for developing cirrhosis estimated at 8.7 in those ALD patients with anti-HCV as compared with those ALD patients without HCV (89). In addition, the presence of HCV is reported to be the major risk factor for the development of hepatocellular cancer (HCC) in patients with alcoholic cirrhosis (90), with a 10-yr absolute cumulative occurrence risk of HCC being reported as high as 81% in anti-HCV-positive alcoholic cirrhotics as compared with 19% in anti-HCVnegative patients (91).…”
Section: Risk Factorsmentioning
confidence: 99%
“…[23][24][25][26] Similarly, despite the initial suggestion that chronic infection with hepatitis C virus (HCV) may multiplicatively interact with alcohol intake in determining cirrhosis, 27 recent evidence suggests that these two factors act independently. 28 The aim of the present study was to assess, using a case-control design, the risk of developing liver cirrhosis associated with alcohol intake, HCV infection, and the combined action of these factors. …”
mentioning
confidence: 99%